Decomposition of Linear Singularly Perturbed Functional Differential Equations - Perestyuk, M.O.; Cherevko, I.M. (Нелінійні коливання, 2001)
We study a system of linear singularly perturbed functional differential equations by using the
method of integral manifolds. We construct a change of variables that decomposes this system
into two subsystems: ordinary differential equation on the center manifold and integral equations on the stable manifold